The Effectiveness of Psychoeducation in Enhancing Future Orientation Among Juvenile Correctional Students - Fathoni, Aryo Bimo; Djamal, Nani; Garnasih, Titi Ratna; Azizah, Nur'aini; Arifah, Fathimah Naimaturrahman (Faculty of Psychology Sunan Gunung Djati Islamic University of Bandung, 2025)
This study aims to examine the effectiveness of psychoeducation in enhancing future orientation among students at a juvenile correctional institution (andikpas) in Bandung, Indonesia. The research employed an experimental method using a pretest-posttest control group design. A total of 50 andikpas were assigned to either an experimental group or a control group, each consisting of 25 participants. Data were collected using a Future Orientation Questionnaire administered before and after the intervention. The results of the Mann-Whitney test indicated a significant increase in scores in the experimental group from pretest (M = 70.03) to posttest (M = 83.33), with p < 0.01, while no significant change was observed in the control group. These findings suggest that psychoeducation is effective in improving the understanding and future readiness of juvenile correctional students.